Penatalaksanaan Terapi Latihan Pada Kondisi Post Caesarean Section DI RSUD dr. Moewardi Surakarta - Norwida, Atika; , Yulisna Mutia Sari, SSt. Ft, M. Sc (GRS) (2015)
Background: Caesarean section is a surgery with making an incision in the abdominal wall as the way out of the baby. With a problematic form of pain, spasm, decreased range of motion, decrease in abdominal muscle strength, and decreased functional activity. Modality which given in these conditions are puerperal gymnastics and transfer ambulation exercise. Objective: To determine the benefits of puerperal gymnastic and transfer ambulation exercise in reducing pain, decrease spasm, increase the strength of the abdominal muscles, improve functional activities. Method: physiotherapy are used in that cases is therapeutic exercise with puerperal gymnastics and tranfer ambulation exercise. The evaluation was done by the method of measurement of pain (VDS), measurement spasm (palpation), measuring of the strength of the abdominal muscles with MMT, and functional activity (Katz Index). Results: After 6 times of therapy showed a decrease in pain silent T1: 4 pain is not so serious into T6: 1 no pain, tenderness T1: 7 unbearable pain became T6: 3 mild pain, pain motion T1: 7 pain becomes heavy enough T6: 3 mild pain; spasm is reduced; increase functional activity that is getting better. Conclusion: In these conditions the modalities of therapeutic exercise such of puerperal gymnastics and transfer ambulation exercise, can reduce pain, increase the strength of the abdominal muscles, decrease abdominal muscle spasm, and increased functional activity. Keywords: Sectio Caesarea, Puerperal Gymnastics, Tansfer ambulation.